Disease activity return after natalizumab cessation in multiple sclerosis. (3rd May 2016) - Rasenack, Maria; Derfuss, Tobias
ABSTRACT: Natalizumab (NAT) was the first monoclonal antibody to be approved for the treatment of relapsing-remitting multiple sclerosis. Its considerable and sustained efficacy has been demonstrated in two phase III studies. However, there are several reasons why its use is limited in clinical practice. The main argument for stopping use of the drug is the risk of the rare but serious progressive multifocal leukencephalopathy. Other reasons are neutralizing antibodies and pregnancy. There is compelling evidence from some clinical trials and many case series that disease activity returns upon suspension or cessation of NAT. Several therapeutic strategies that have been tested to prevent or reduce the recurrence of disease activity will be reviewed in this article. Considering these data, it is evident that the decision to stop NAT treatment has different implications and consequences. A subsequent therapy after cessation of NAT is needed to reduce the risk of disease recurrence.